(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Chatbots allow consumers to access information and services using a conversational interface. Medical care is vital to everyone. Counseling a physician for every medical issue is difficult. We want to create an AI-powered healthcare chatbot that can identify and deliver basic disease information before seeing a doctor. The NLP algorithm is used. AI-powered NLP analyzes and understands natural human language in our Chatbot. The solution makes bot-user communication easy with text-text support. Based on user symptoms, the Chatbot suggests disease treatments. Chatbot rates the disease as severe or negligible based on symptoms. If the illness is severe, the user is encouraged to see a doctor, and if it is minor, it provides medical aid. Our method uses the patient’s symptoms to assist them choose the right antibiotics and precautions. The Python package NLTK (Natural Language Toolkit) does symbolic and statistical Natural Language Processing for English written in programming. It analyzes speech input and generates human-like answers.